(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
this article analyzes the digital transformation of the food supply of military educational institutions in the conditions of the innovative economy. In order to study the existing problems in military educational institutions, questionnaires, interviews and social surveys were conducted and analyzed. In order to eliminate the existing problems, digitization, i.e. digital transformation of the military educational institution, has been developed as a solution to the problem.